Global environmental governance : considerations for a way forward for the Commonwealth - Yusuf, Nageela (Commonwealth Policy Studies Unit [London], 2009)
Considers the role that Commonwealth Environment Ministers could play in driving the agenda for effective global environmental governance (GEG). Deals with GEG leadership and looks at the greater role non-state actors could play in the development of GEG policy and policy implementation.